Utilizing Chaotic Logistic Keys for LSB1 and LSB2 Message Steganography - Sharadqh, Ahmad A.; Alkasassbeh, Jawdat S.; Alawneh, Tareq A.; Al-Qaisi, Aws; Makableh, Yahia F.; Al Adwan, Safaa (Engineering, Technology & Applied Science Research, 2024)
This paper introduces a novel hybrid data steganography method that combines the new techniques of LSB1 and LSB2. The proposed method simplifies data-hiding and extraction operations by utilizing a patch method. A unique Private Key (PK) divides the message into two parts. The first part is processed using the LSB1 method, while the second one is treated with the LSB2 method. The PK information is utilized to create secret keys, namely key1 and key2. The keys are generated by converting two Chaotic Logistic Keys (CLKs) and establishing the sequence of cover Stego bytes for concealing and revealing data. The secret message is protected within a secure key area by utilizing the PK, which improves security by preventing unwanted access. The secret message’s effective extraction depends significantly on the PK’s content. Any alterations to the key during the extraction step will be deemed unlawful, possibly leading to a compromized secret key. Moreover, the suggested approach is followed and assessed by using different messages. The results are comprehensively studied, ensuring a robust evaluation of the quality, efficiency, and security improvements of the data steganography process. The experimental results confirm the data steganography’s quality, efficiency, and security enhancements.